2023
DOI: 10.3389/fimmu.2023.1107559
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture and human iPSC-derived small extracellular vesicles regulate the gut microbiota in ischemic stroke via the brain-gut axis

Abstract: Electroacupuncture (EA) and induced pluripotent stem cell (iPSC)-derived small extracellular vesicles (iPSC-EVs) have substantial beneficial effects on ischemic stroke. However, the detailed mechanisms remain unclear. Here, we explored the mechanisms underlying the regulation of EA and iPSC-EVs in the microbiome-gut-brain axis (MGBA) after ischemic stroke. Ischemic stroke mice (C57BL/6) were subjected to middle cerebral artery occlusion (MCAO) or Sham surgery. EA and iPSC-EVs treatments significantly improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 74 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…After cerebral ischemia, the gut microbiota further damages the immune system and aggravates intestinal and brain damage ( Wang et al, 2022 ). Electroacupuncture has been shown to regulate intestinal immunity through MGBA, reducing brain and colon damage after cerebral ischemia and positively affecting the outcome of ischemic stroke and preventing its occurrence ( Li et al, 2022 ; Zhang et al, 2023 ). #3: Cognitive dysfunctions such as memory, attention, judgment, executive functioning, and calculation are common complications for patients in the middle, which leads to a reduced quality of life ( Liu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…After cerebral ischemia, the gut microbiota further damages the immune system and aggravates intestinal and brain damage ( Wang et al, 2022 ). Electroacupuncture has been shown to regulate intestinal immunity through MGBA, reducing brain and colon damage after cerebral ischemia and positively affecting the outcome of ischemic stroke and preventing its occurrence ( Li et al, 2022 ; Zhang et al, 2023 ). #3: Cognitive dysfunctions such as memory, attention, judgment, executive functioning, and calculation are common complications for patients in the middle, which leads to a reduced quality of life ( Liu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…This theory posits the existence of a bidirectional information pathway connecting the brain and the gut, with gut microorganisms and their metabolites playing a crucial role in this pathway, thereby constituting the MGBA. Evidence has demonstrated that the exchange of information and transmission of transmitters between the brain and the gut exert an influence on the onset and progression of specific cerebrovascular diseases, including ischemic stroke ( Zhang et al, 2023 ). However, there is a limited amount of literature available regarding the involvement of MGBA in ICH.…”
Section: Discussionmentioning
confidence: 99%
“…Damage to the CNS has been observed to coincide with alterations in gut microbiota, while changes in the abundance of gut microbiota have also been found to impact the CNS. The involvement of gut microbiota in the pathogenesis and progression of diseases such as Alzheimer’s disease ( Liu et al, 2020 ), Parkinson’s disease ( Chandra et al, 2017 ), and ischemic stroke ( Zhang et al, 2023 ) have been established, although limited research exists regarding its role in cerebral hemorrhage. This review critically examines previous literature pertaining to the manipulation of the MGBA for the treatment of ICH, and explores potential proteins that hold promise as therapeutic targets, thereby offering novel avenues for the future management of ICH.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, the data point to the possibility of improving impaired glucose metabolism, halting the course of AD, and reducing neuroinflammation by modulation of gut microbiota employing probiotics in AD, which would then enhance the benefits of GLP-1. The second most common and first among neurodegenerative illnesses is PD (Hong et al, 2023). A variety of motor and nonmotor symptoms, including synuclein accumulation and the progressive degradation of dopaminergic neurons, are associated with the condition.…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%